Audit and Sustainability: Integrating Environmental Aspects in Auditing - Pramukti, Andika (Manunggal Halim Jaya, 2024)
This study explores the integration of environmental aspects into auditing practices, aiming to enhance organizational sustainability and corporate governance. Through a systematic review of literature, the historical evolution of environmental auditing is traced from its roots in the late 20th-century sustainability movement to its prominence in the early 2000s within the accounting profession. Theoretical frameworks such as institutional theory and legitimacy theory are employed to understand the drivers behind organizations' adoption of environmental auditing practices. Challenges hindering the effective integration of environmental aspects into auditing practices, including the lack of standardized methodologies and regulatory complexity, are identified. Despite these challenges, environmental auditing presents opportunities for organizations to improve their environmental performance, mitigate risks, and identify opportunities for improvement and innovation. Future research directions include exploring innovative methodologies for assessing environmental performance, addressing regulatory challenges, investigating auditors' roles in promoting sustainability, and conducting longitudinal studies to assess the long-term impact of environmental auditing on organizational performance. The study underscores the importance of advancing sustainable auditing practices to achieve organizational sustainability goals.